Gendering the Master Narrative : Women and Power in the Middle Ages - Kowaleski, Maryanne; Erler, Mary Carpenter (Book collections on Project MUSE., 2003)
Gendering the Master Narrative asks whether a female tradition of power might have existed distinct from the male one, and how such a tradition might have been transmitted. It describes women's progress toward power as a push-pull movement, showing how practices and institutions that ostensibly enabled women in the Middle Ages could sometimes erode their authority as well. This book provides a much-needed theoretical and historical reassessment of medieval women's power. It updates the conclusions from the editors' essential volume on that topic, Women and Power in the Middle Ages, which was published in 1988 and altered the prevailing view of female subservience by correcting the nearly ubiquitous equation of "power" with "public authority." Most scholars now accept a broader definition of power based on the interactions between men and women. In their Introduction, Mary C. Erler and Maryanne Kowaleski survey the directions in which the study of medieval women's agency has developed in the past fifteen years. Like its predecessor, this volume is richly interdisciplinary. It contains essays by highly regarded scholars of history, literature, and art history, and features seventeen black-and-white illustrations and two maps